Direct and Pollinator-Mediated Effects of Herbivory on Strawberry and the Potential for Improved Resistance - Muola, Anne; Weber, Daniela; Malm, Lisa E.; Egan, Paul A.; Glinwood, Robert; Parachnowitsch, Amy L.; Stenberg, Johan A. (Frontiers in Plant Science, 2017)
The global decline in pollinators has partly been blamed on pesticides, leading some to propose pesticide-free farming as an option to improve pollination. However, herbivores are likely to be more prevalent in pesticide-free environments, requiring knowledge of their effects on pollinators, and alternative crop protection strategies to mitigate any potential pollination reduction. Strawberry leaf beetles (SLB) Galerucella spp. are important strawberry pests in Northern Europe and Russia. Given that SLB attack both leaf and flower tissue, we hypothesized pollinators would discriminate against SLB damaged strawberry plants (Fragaria vesca, cultivar ‘Rügen’), leading to lower pollination success and yield. In addition we screened the most common commercial cultivar ‘Rügen’ and wild Swedish F. vesca genotypes for SLB resistance to assess the potential for inverse breeding to restore high SLB resistance in cultivated strawberry. Behavioural observations in a controlled experiment revealed that the local pollinator fauna avoided strawberry flowers with SLB-damaged petals. Low pollination, in turn, resulted in smaller more deformed fruits. Furthermore, SLB-damaged flowers produced smaller fruits even when they were hand pollinated, showing herbivore damage also had direct effects on yield, independent of indirect effects on pollination. We found variable resistance in wild woodland strawberry to SLB and more resistant plant genotypes than the cultivar ‘Rügen’ were identified. Efficient integrated pest management (IPM) strategies should be employed to mitigate both direct and indirect effects of herbivory for cultivated strawberry, including high intrinsic plant resistance.